1993
DOI: 10.1111/j.1365-3024.1993.tb00598.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of mouse/human chimaeric antibodies to investigate the roles of different antibody isotypes, including lgA2, in the killing of Schistosoma mansoni schistosomula by eosinophils

Abstract: We report the use of a matched set of mice/human chimaeric antibodies, directed against the 5-iodo-4-hydroxyl-3-nitrophenacetyl (NIP) hapten, to investigate the roles of different human isotypes in antibody-mediated eosinophil-dependent killing of schistosomula. The chimaeric antibodies consist of mouse VH, VL and CL regions with human gamma 1, gamma 2, gamma 3 (2 allotypes), gamma 4, alpha 2, mu or epsilon CH regions and were used in in vitro assays with human eosinophils and NIP-coated S. mansoni schistosomu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Like the other FcRs associated to ITAMs, cross-linking of FcaR via Fc fragments of IgA triggers several biological responses which seem to be dependent on the cell type in the myeloid lineage. These responses, which are generally mediated by Ca 2z mobilization and PKC activation [97], include phagocytosis of IgA immune complexes [120,121], antibody-dependent cell-mediated cytotoxicity [120], killing of IgAopsonized bacteria and parasites [122][123][124], and production of reactive oxygen intermediates [64,125,126], inflammatory mediators and cytokines [127], as well as leukotrienes and prostaglandins [128]. Crosslinking of FcaR by IgA complexes on monocytes induces an increased production of TNF-a, IL-1b and IL-6 [99,[128][129][130].…”
Section: Immunoglobulin-a Leukocyte Receptor-mediated Leukocyte Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Like the other FcRs associated to ITAMs, cross-linking of FcaR via Fc fragments of IgA triggers several biological responses which seem to be dependent on the cell type in the myeloid lineage. These responses, which are generally mediated by Ca 2z mobilization and PKC activation [97], include phagocytosis of IgA immune complexes [120,121], antibody-dependent cell-mediated cytotoxicity [120], killing of IgAopsonized bacteria and parasites [122][123][124], and production of reactive oxygen intermediates [64,125,126], inflammatory mediators and cytokines [127], as well as leukotrienes and prostaglandins [128]. Crosslinking of FcaR by IgA complexes on monocytes induces an increased production of TNF-a, IL-1b and IL-6 [99,[128][129][130].…”
Section: Immunoglobulin-a Leukocyte Receptor-mediated Leukocyte Responsementioning
confidence: 99%
“…This is a relevant effect, especially at mucosal surfaces where the inflammatory response and released cytokines following bacterial adherence and/or invasion can stimulate both FcaR expression and phagocytosis of IgAopsonized particles by PMN [131]. FcaR also plays an important role in eosinophil degranulation [132] and killing of parasites such as schistosomes [124]. In addition, eosinophils may also bind SIgA via a specific receptor for SC and therefore constitute potential candidates in host mucosal defence against parasite invasion.…”
Section: Immunoglobulin-a Leukocyte Receptor-mediated Leukocyte Responsementioning
confidence: 99%
“…The cleavage of IgE by schistosomes into a molecule which is unable to engage FcεRII receptors is likely to be an important immune evasion strategy employed by the parasite, and may partially explain why IgA has been observed to be more effective at killing schistosomula than IgE in vitro [41]. The demonstration that IgE cleavage is most likely attributable to the schistosomal elastase will stimulate interest in this enzyme as an important target for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4 has no cytotoxic activity and can block the effects of IgG1, IgG2, and IgG3 (13). Furthermore, other studies have indicated a role for IgE and IgA in the elimination of schistosomula through similar mechanisms (14,15).…”
mentioning
confidence: 92%